Fertility management of Klinefelter syndrome. Issue 6 (2nd November 2019) - Fainberg, Jonathan; Hayden, Russell P.; Schlegel, Peter N.
ABSTRACT: Introduction : Klinefelter syndrome (KS) represents the most common chromosomal abnormality in the general population, and one of the most common genetic etiologies of nonobstructive azoospermia (NOA) and in severe oligospermia. Once considered untreatable, men with KS and NOA now have a variety of treatment options to obtain paternity. Areas covered : The cornerstone of treatment for both KS and NOA patients remains the surgical retrieval of viable sperm, which can be used for intracytoplasmic sperm injection to obtain pregnancy. Although the field has advanced significantly since the early 1990s, approximately half of men with KS will ultimately fail fertility treatments. Presented is a critical review of the available evidence that has attempted to identify predictive factors for successful sperm recovery. To optimize surgical success, a variety of treatment modalities have also been suggested and evaluated, including hormonal manipulation and timing of retrieval. Expert opinion : Individuals with KS have a relatively good prognosis for sperm recovery compared to other men with idiopathic NOA. Surgical success is heavily dependent upon surgical technique and the experience of the andrology/embryology team tasked with the identification and use of testicular sperm.